PENGARUH KEBUTUHAN, PELAYANAN DAN JAMINAN TERHADAP PEMANFAATAN JASA PERMODALAN DI KECAMATAN NAGA JUANG - Siti Kholijah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
This study aims to determine the effect of the needs factor, guarantee factor and service factor on the community in utilizing the Mekaar Program Civil National Capital Service (PNM) in Sayur Matua Village, Naga Juang District. The population in this study were all residents who received funding from the Mekaar Program Civil National Capital (PNM) in Sayur Matua Village, Naga Juang District, as many as 121 customers with a sample of 55 respondents. The data collection technique for this research was a questionnaire which was tested for validity and reliability. Data analysis techniques using multiple linear regression, classical assumption test, t test, F test and the coefficient of determination. The magnitude of the influence of the need on public interest in utilizing the Mekaar Program Civil National Capital Services (PNM) is 0.236 or 23.6%, the magnitude of the collateral effect on public interest in utilizing the Mekaar Program Civilian National Capital Services (PNM) is 0.366 or 36.6%, and the magnitude of the influence of the service on public interest in utilizing the Mekaar Program's Civil National Capital Service (PNM) is 0.433 or 43.3%. While the results of the F test show that the significance value is 0.000 <0.05 and the calculated f value is 257.020 > f table 2.79, it can be concluded that the variables of needs, guarantees and services have a significant effect simultaneously on people's interest in utilizing the Civil National Capital Services (PNM ) Mekaar Program. obtained an R square value of 0.938 or 93.8%. This shows that the variables of needs, guarantees and services have an effect of 93.8% on people's interest in utilizing the Mekaar Program's Civil National Capital Services (PNM), while the remaining 6.2% is influenced by other variables or factors outside of research.